Principle of Choice of Customs Procedure in EU Customs Traffic (Frontiers in Law, 2023)
The research topic of the article focuses on the analysis of the principle of choosing a customs procedure in EU customs trade, which is of a normative nature. It is also the basic method of dealing with goods. In addition to the general legal principles constituting this principle, the article discusses the principle of freedom of trade in goods abroad; the principle of equal treatment of entities; the principle of equal treatment of goods; the principle of universality of customs duties and customs fees; the principle of universal access to information on customs law; the principle of non-revokability of the customs declaration. The conditions for export and import customs procedures were also discussed.